COMPUTED TOMOGRAPHIC ARTHROGRAPHY OF THE NORMAL CANINE ELBOW. Issue 2 (25th August 2014) - Gendler, Andrew; Keuler, Nicholas S.; Schaefer, Susan L.
<x xml:space="preserve">Abstract</x> Comprehensive evaluation of canine elbow joint dysfunction includes assessment of articular cartilage, which can noninvasively be performed with contrast arthrography. Aims of this prospective study were to compare positive contrast computed tomographic (CT) arthrography and histomorphometry measures of cartilage thickness in normal canine elbows, and to determine the optimal contrast medium concentration. Thirty‐two canine cadaver elbows were examined using multidetector CT, before and after intra‐articular administration of iohexol at one of three different concentrations. Articular cartilage thickness was measured on both the CT arthrography images and corresponding histologic specimens. Mean difference (bias) between the CT arthrography and histomorphologic measurements was 0.18 and 0.19 mm in the sagittal and dorsal planes, respectively. Mean bias and precision of CT arthrography measurements made in the sagittal or dorsal reformations were not significantly different from one another. Computed tomographic arthrography measurements from elbows with 75 mg I/ml were significantly larger and had greater bias compared to other contrast medium groups (150 and 37.5 mg I/ml). There was no significant difference in CT arthrography measurement precision between different contrast medium concentrations. Histomorphologic thickness of the articular cartilage overlying the cranial aspect of the ulna (mean 0.32 mm) was significantly thinner than cartilage of the radius (0.36 mm) or humerus (0.36 mm). Findings from this cadaver study indicated that CT arthrography delineates articular cartilage of the normal canine elbow; yields cartilage thickness measures slightly greater than histomorphometry measures; and provides high measurement precision regardless of image plane, contrast medium concentration, or anatomic zone.